Effective C : an introduction to professional C programming - Seacord, Robert C. (No Starch Press, Inc., 2020)
"An in-depth guide for developers who already know how to program and want to quickly come up to speed on professional programming in C. It introduces the language's basic data types and code structures ; addresses best practices and common errors ; and teaches how to debug, test, and analyze C programs"